Vertical distribution of meiofauna on reflective sandy beaches - Martins,Mariana de Oliveira (2015)
Abstract Extreme physical conditions usually limit the meiofauna occurrence and distribution in highly hydrodynamic environments such as reflective beaches. Despite sediment grains of the upper layers being constantly resuspended and deposited, the high energy of the swash zone besides depositing coarse sediments allows an ample vertical distribution of meiofaunal organisms. The effect of physical, chemical and sediment variables on the vertical distribution of meiofaunal organims and nematodes was analysed on two reflective exposed beaches. Sampling was conducted at three sampling points on each beach in the swash zone. The sediment collected was divided into four 10-cm strata (0-10 cm, 10-20 cm, 20-30 cm, 30-40 cm). The statistical differences between strata due to factors previously established (i.e. meiofaunal composition, density of most abundant taxa) were tested using a hierarchical PERMANOVA applied under similarity and euclidian distances. An inverse relation among average grain size, content of organic matter and sediment sorting was evident. Coarser sediment characterized the upper layers, while at deeper layers the sediment was very poorly sorted and presented a higher content of organic matter. A similar pattern in the vertical distribution of meiofaunal and nematofaunal composition and density was detected. The lowest densities were associated with the first stratum (0-10 cm), highly affected by hydrodynamics. The vertical distribution of organisms was statistically different only when the interaction among factors was considered. This result suggests that zonation and vertical distribution of meiofaunal organisms are determined by the within-beach variability.